APPARATUS REALIZATION OF BIOMECHANICAL DIAGNOSTICS OF CARDIOVASCULAR SYSTEM BASED ON OSCILLOMETRY - V. V. Shevtsov; S. V. Shilko; M. V. Borisenko; Yu. G. Kuzminsky (Приборы и методы измерений)
The apparatus requirements and preliminary results of development of special program and apparatus system «SPAS» for heart and blood vessels diagnostics by oscillometry method have been described. The estimation of apparatus realization using PIC16f870i/sp controller have been given.